Clinical forensic medicine examination of trafficked victims - Alempijević Đorđe M.; Savić Slobodan; Ječmenica Dragan S.; Aleksandrić Branimir (Temida)
In this paper certain explanations of health related aspects of human trafficking are discussed together with responsibilities of health care providers to the victims of trafficking. Clinical forensic medicine is outlined, and its role in obtaining of medical evidence has been discussed. Special remarks are made on the application of clinical forensic medicine skills in assessment of victims of human trafficking. Protocol for clinical forensic examination of the victims of human trafficking, which has been developed in the Institute of Forensic Medicine in Belgrade, has been discussed in details.